THE ROLE OF MULTIMEDIA TECHNOLOGY (LAVIR-VIRTUAL LABORATORY) IN DEVELOPING LIFE SKILLS IN VOCATIONAL SCHOOLS - Haryoko, Sapto; Jaya, Hendra (MATTER: International Journal of Science and Technology, 2018)
The aim of research is to conduct a practicum, the school will need several factors which are a laboratory for each practical subject, equipment facilities and complete practicum material. Students hope to gain more knowledge and experience as study results, while teachers, on the other hand, expect that practical learning process can bring achievement in term of better cognitive, psychomotor, affective changes, and improvement of student life skill. It was found that the use of this Virtual Laboratory Model by SMK students can develop their life skills such as personal skills, thinking skills, social skills, and vocational skills. For Personal Skills, the mean score of test is 4.14 (good), Thinking Skills mean score is 4.06 (good), Social Skills mean score is 4.32 (very good), and for vocational skills, the score is 4.30 (very good). Furthermore, in this study, it was also found that data or information on the process of learning life skills (life skills) consists of several aspects: (1) aspects of planning, include: curriculum, financial and facilities; (2) aspects of implementation, including: methods and techniques, media, competence tutor, materials or teaching materials, and time / schedule; (3) aspects of evaluation, including assessment of learning outcome. After producing a virtual laboratory model, this research carried out trial test on the developed product to several students of partner SMKs and other SMKs in Makassar.